Nothing left to learn: Translation and the Groundhog Day of bureaucracy. Issue 5 (November 2016) - Izak, Michal
Beyond the existing theorizing of translation as a creative disruption in both occupational and semantic terms, this study explores it critically in the experiential framework of professional translators and as a meaning-making process. Acknowledging the role of translation in creating dialogic and radical climates for learning, the article proposes to explore the other side of this relationship by studying how the limiting of space for translation delimits the possibilities for meaning-creation, thus precluding dialogue. In addition to this general point, it ponders the specific aporia of organizationally embedded adversity of translation in the occupational context (apparently) devoted to semantic labour, namely that of translator's work. It demonstrates that the rigidity of meaning-making and the inexorableness of partaking in the uncanny déjà vu are the reflections of specific organizational (bureaucratic) frame and posits that they may be used as experiential and semantic heuristics for better understanding learning and non-learning in organizations.